Facial expressions perceived by the adolescent brain: Towards the proficient use of low spatial frequency information - Peters, Judith C; Kemner, Chantal (Elsevier, 2017)
Rapid decoding of emotional expressions is essential for social communication. Fast processing of facial expressions depends on the adequate (subcortical) processing of important global face cues in the low spatial frequency (LSF) ranges. However, children below 9 years of age extract fearful expression information from local details represented by high SF (HSF) image content. Our ERP study investigated at which developmental stage this ineffective HSF-driven processing is replaced by the proficient and rapid LSF-driven perception of fearful faces, in which adults are highly skilled. We examined behavioral and neural responses to high- and low-pass filtered faces with a fearful or neutral expression in groups of children on the verge of pre-adolescence (9-10 years), adolescents (14-15 years), and young adults (20-28 years). Our results suggest that the neural emotional face processing network has a protracted maturational course into adolescence, which is related to changes in SF processing. In mid-adolescence, increased sensitivity to emotional LSF cues is developed, which aids the fast and adequate processing of fearful expressions that might signal impending danger.
Keywords: Adolescence; ERP; Emotional face perception; Neurobiological development; Spatial scales; Taverne; General Neuroscience; Neuropsychology and Physiological Psychology